NADA POLIFONIK TEKS MARXIST ALA KUNTOWIJOYO: PENCARIAN JATI DIRI DARI MARXISME KE ISLAM - Makin, Al (Jurnal Sosiologi Reflektif, 2019)
This paper presents the way in which Kuntowijoyo searches for an epestimological formulation and critical thinking from Marxits to Islamic tendencies. This effort fills the gap left by some Indonesian readers of Kuntowijoyo’s works who only highlight his Islamic ideas in literature, culture, history, and sociology from which Kuntowijoyo unleashes the idea of prophetic paradigmn to differentiate his thought from secular Western mode of thinking.  This paper also compares Kuntowijoyo’s text to the performance dangdut music of Rhoma Irama to discover the tone and rhytm of polyphone, by which I mean complexity of the text in combining Western and Eastern thoughts. This writing sheds light on the polyphonic tone of Kuntowijoyo’s text and the shifting paradigm of his thought from Marxist to Islamic tendencies.Tulisan ini membahas pergulatan pemikiran Kuntowijoyo dari aliran Marxist menuju arah Islamis. Dalam tulisan ini menyoroti para pembahas di Indonesia yang sering menekankan gagasan islami Kuntowijoyo dalam sastra, budaya, pemikiran sejarah dan sosiologi, terutama gagasan tentang profetiknya dalam bidang-bidang tersebut. Tulisan ini sekaligus membandingkan teks polifonik Kuntowijoyo yang meramu tradisi Marxisme Barat dengan musik dangdut Rhoma Irama sebagai tolak ukur nada dan irama polifonik. Baik musik dangdut ataupun teks Kuntowijoyo menghadirkan berbagai unsur perpaduan Barat dan Timur dan sekaligus mengarah pada pencarian identitas keislaman Kuntowijoyo dan Rhoma Irama. Tulisan ini sekaligus memberi sumbangan baru pada pembacaan teks polifonik dan pergeseran gagasan Kuntowijoyo dari Marxist ke Islami yang tidak mendapatkan porsi cukup dari para pembahas di Indonesia.